Upper tail of the income distribution in tax records and survey data. Evidence from Poland - Kośny, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
Growing interest in the situation of the rich and in changes in the upper tail of the income distribution entails search for specialized sources of data. The majority of available data come from surveys, which are burdened with the problem of the reluctance of the rich to reveal their income and assets. This is the incentive to look for alternative data sources. One of such sources are tax records. Irrespective of their credibility (limited by tax avoidance and tax evasion), the crucial feature of data collected by tax offices is its completeness for the population of taxpayers: refusal to file a tax return or providing false information is punishable by law. The paper compares the data gathered within the Household Budget Survey, which is commonly used for research and administrative purposes in Poland, with the complete dataset of tax records for Dolnośląskie province (over 2 million taxpayers). Analyses show large discrepancies in the results obtained for both datasets in the upper tail of the income distribution. The observed differences are important for the proper assessment of the actual situation of the rich
Argumenta Oeconomica, 2019, Nr 1 (42), s. 55-80
Keywords: affluence; top incomes; survey data; tax records